Digital Risk Management Practices among Indonesians Startups - Rasyidwan, Faizal (Omnia Tempus, 2025)
This study aims to explore the digital risk management practices among Indonesian startups, with a focus on understanding the challenges, strategies, and effectiveness of their risk mitigation approaches. As digital transformation continues to reshape the startup ecosystem, managing digital risks such as cybersecurity threats, data privacy concerns, and technological obsolescence has become critical for the survival and growth of startups. A qualitative research methodology was employed, using a literature review approach to synthesize findings from recent studies, reports, and industry insights. The research identifies the unique digital risks faced by Indonesian startups and evaluates the strategies they implement to address these challenges. The findings suggest that while Indonesian startups are increasingly aware of digital risks, their approaches to risk management are still in early stages and vary significantly based on the startup's size, resources, and sector. Key strategies include the use of cloud computing, investment in cybersecurity tools, and employee training in data privacy practices. However, significant barriers such as a lack of skilled professionals, financial constraints, and regulatory uncertainty continue to hinder the full adoption of comprehensive digital risk management practices. The study also highlights the role of emerging technologies, such as artificial intelligence and blockchain, in mitigating digital risks. The findings contribute to both theoretical and practical understandings of digital risk management in startups, offering insights into the specific challenges and solutions relevant to startups in emerging markets like Indonesia. This research has important implications for policymakers, startup managers, and future studies in digital risk management.